TRFLP analysis for revealing the diversity of rice phyllosphere bacteria - SRI MARTINA WIRASWATI; ARIS TRI WAHYUDI; IMAN RUSMANA; ABDJAD ASIH NAWANGSIH (Society for Indonesian Biodiversity, 2018)
Wiraswati SM, Wahyudi AT, Rusmana I, Nawangsih AA. 2018. TRFLP analysis for revealing the diversity of rice phyllosphere bacteria. Biodiversitas 19: 1743-1749. Phyllosphere environment of rice plant is usually inhabited by diverse bacteria which mostly contribute beneficial effects to the plant fitness. TRFLP method is a rapid and straightforward method to determine the bacterial diversity of many environments, including rice phyllosphere environment. This study aimed to analyze rice phyllosphere bacterial diversity of healthy rice plant cultivar Ciherang obtained from Sukabumi, Jasinga, and Situgede. The bacterial genomes were amplified and digested with two restriction enzymes, i.e., MspI and BstUI. The bacterial diversity (H’ index) and evenness (E index) were calculated from the peak value. From TRFs analysis, Betaproteobacteria and Pseudomonadales were dominantly found in nearly all samples with different relative abundance. In addition, Alphaproteobacteria and Gammaproteobacteria were also dominant in the several samples. The unique bacteria groups were inhabited in the sample from specific regions with certain growth phase. This finding informs us that the geographical factors might be more influent than the growth phase factor. Furthermore, the bacterial diversity and evenness of the metagenomic approach are higher than cultivation-dependent approach.